Bioimpedance indicators of combat athletes depending on the somatotype - Guryeva, A. B.; Alekseeva, V. A.; Golderova, A. S.; Osinskaya, A. A.; Sergina, E. P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to establish bioimpedansometric indicators of the body of combat athletes in Yakutia, depending on the somatotype according to the Ries-Eysenck index.